Evaluasi Ketahanan Tinta UV Magenta terhadap Durasi Paparan Sinar Ultraviolet pada Media Banner Flexi - Cintana Tsaltsa Syahara; Yoga Putra Pratama; Rachmah Nanda Kartika (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The color fastness of ultraviolet (UV) ink on outdoor print media is a crucial aspect that affects long-term visual quality. This study aims to evaluate the effect of varying the duration of UV exposure on the color stability of UV magenta ink applied to flexi-based banner media. The testing process was carried out experimentally through artificial irradiation, with color change analysis using the CIE Lab color system and the ΔE parameter as an indicator of degradation. The results showed that the longer the irradiation duration, the higher the ΔE value produced, which indicated significant color degradation. This finding emphasizes the importance of applying additional protection, such as UV lamination coating, to improve the color fastness of prints for outdoor use.